Causal Comparative and Correlational Research Designs in Education - Nisa, Rafika (PT Ilmu Inovasi Nusantara, 2025)
This research aims to explain the definition, objectives, characteristics, as well as the advantages and disadvantages of causal comparative and comparative research. This research is qualitative research using a literature review method. This research is certainly very important to study, especially for education researchers who want to study cause and effect and colleration in various variables in the field of education. The results of this research are causal-comparative and correlational research may be confused because both studies are without manipulation and the same thing regarding the interpretation of results. There is a difference between the two, namely that comparative causal studies usually involve two or more groups and one independent variable, while correlational studies usually involve two or more variables and one group. Comparative causal studies involve comparisons, while correlational studies involve correlations.